An Overview on the Conversion of Forest Biomass into Bioenergy - Yu, Qing; Wang, Yacheng; Van Le, Quyet; Yang, Han; Hosseinzadeh-Bandbafha, Homa; Yang, Yafeng; Sonne, Christian; Tabatabaei, Meisam; Lam, Su Shiung; Peng, Wanxi (Frontiers in Energy Research, 2021)
Biomass energy helps to alleviate the fossil energy crisis as renewable energy. In this review, we discuss and compare the direct combustion of forestry biomass into a specific boiler suitable for biomass combustion with the combustion of forestry biomass compressed into wood pellets and discuss the subsequence conversion process of forestry biomass into biodiesel and biogas. By burning forestry biomass, a small power plant may transform up to 140,000 tons of the biomass into 620000 kWh which reduce greenhouse gas emissions of 40,500 tons and generate power for 10000 average households. Being a feedstock to promote renewable technology and bioeconomy, forestry biomass mainly composes of cellulose, hemicellulose and lignin that can be converted into biofuels including biodiesel and biogas using catalytic cracking and pyrolysis techniques. Although conversion of forestry biomass helps to alleviate the shortage and environmental challenges of fossil energy, this application is not fully explored. Therefore, expanding the market demand of forestry biomass is an effective solution, and the construction of machinery, factories and related products using forestry biomass is the premise of making full use of forestry biomass.